Reactive mobility by failure - Zunino, Alejandro (2003)
Mobile agent development is mainly supported by Java-based platforms. However, the weak mobility model they use, added to the inherent complexity of building location-aware software, impose strong limitations for developing mobile agents. In this article we present MoviLog, a platform for building Prolog-based mobile agents with a strong mobility model. The major contribution of MoviLog is its Reactive Mobility by Failure (RMF) mechanism. MRF is a mechanism that acts when an agent needs a resource that is not available at the current executing site. RMF uses a distributed multi-agent system to transparently transport the executing agent to the site where the resource is available, thus reducing the development effort with respect of traditional platforms, while maintaining its advantages